(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Over the centuries, many cultural and artistic trends have taken place. In particular, the moments of transition from one era to another have been considered as secondary for their participation both in the past and in the present. In this sense, an emblematic case study seems to be recognized in the eighteenth century. In fact, the progressive abandonment of the Baroque language in favour of a more austere and moderate line just represented the initial phase of a more marked change of tastes that turned up into Neoclassicism. Nonetheless, this style was born in contradiction with itself because this need of absolute rationality soon joined the frustration that this determined, opening new unexpected scenarios. This was the condition of the post-baroque man: projected towards an uncertain future but in need of abandoning the past.